Hard-hydrophobic nano-CuO coating via electrochemical oxidation for heat transfer performance enhancement - Mahmood, M. H.; Maleque, Md. Abdul; Rahman, M.M. Hafizur (Springer, 2022)
The heat transfer performance of the material is mainly affected by the surface-to-volume ratio and specific surface area. This paper presents an evaluation of hard-hydrophobic nano-CuO coating on the heat transfer performance of copper material. The nano-CuO coating was de-veloped using the electrochemical oxidation method in 0.1 M oxalate solution at ambient temperature. The nano-CuO coating was character-ized using electrical resistivity (ER) meter, X-ray diffraction (XRD), energy dispersive X-ray Spectroscopy (EDX), and field emission scanning electron microscopy (FESEM). The average grain size of the coated material was ~45 nm with an average coating thickness of 15 μm. The thermal resistance of the nano-CuO coated sample was lower than the uncoated sample with the increased thermal conductivity. The nano-CuO coating demonstrated a hard-hydrophobic characteristic feature on the surface with the maximum hardness attainment of 178 Hv. The nano-coating also enhanced the efficiency of heat transfer (Eff %) by ~95%. This enhancement is due to the increasing of the spe-cific surface area by 272 times which in turn increases heat transfer performance across the nano-coated surface about 22 times as compared to the uncoated surface. This result confirmed the feasibility of this current hard-hydrophobic nano-CuO coating for enhancement of hard-ness, hydrophobicity, and heat transfer performance of copper material in the cooling and heating technology especially for the reduction of the required size of heat transfer equipment, increasing reliability, and improvement of surface protection characteristics.